Colonic adenocarcinoma an underlying malignancy of dermatomyositis: case report - García-Cerda, Daniel; Vazquez-Camacho, Mabi; Carrillo-Manguart, Valeria; Marín-Rosales, Miguel; Torre, Ignacio Garcia-de la (International Journal of Research in Medical Sciences, 2023)
Idiopathic inflammatory myopathies (IIM) are a heterogeneous group of chronic, autoimmune connective tissue disorders that affect muscles primarily. A few cases have reported the correlation between IIM and paraneoplastic manifestations, primarily dermatomyositis (DM). We described the case of a 47-year-old woman with dermatomyositis and the finding of a colonic adenocarcinoma, who presented alternating diarrhoea and hematochezia. The immunoassay for myositis-specific antibodies showed anti-Mi-2a, anti-MDA5, and anti-Ro52 antibodies, while the colonoscopy showed a one-centimetre mass in the sigmoid. Literature reviews have contemplated an underlying malignancy in patients with dermatomyositis, particularly in those with anti-Mi-2 antibodies and atypical features or unexplained symptoms. A correlation between DM and colonic adenocarcinoma has-been documented in a few reports, particularly in patients with unexplained gastrointestinal symptoms or weight loss. The mechanisms of the association of dermatomyositis and malignancies, especially colonic malignancies, are still unknown and need more research for better strategies.